Apocalypses ouvrières. Théâtre, SF et critique sociale dans les années 1920 - Isabelle Krzywkowski (ReS Futurae)
The article considers an international corpus of plays from the 1920s-1930s that have the characteristic of combining the theme of work with anticipation. The failure of machines and the «  robotization  » of workers : this combination raises questions about the future of a world that is increasingly subject to mechanical development. After pointing out that the effect of anticipation is based essentially on the stage settings and the uniformity of the characters, the article discusses the critical significance of this repertoire : the threats posed to humanity by the development of technology (industrial disasters, loss of the meaning of work) give this theatre a dystopian character, barely modulated by the progressive perspective of the disappearance of work, which is however not defended by the workers. It is therefore a double apocalypse that these plays depict : that of the labour world, due to the generalisation of machines that replace man, but also to the passivity of workers ; and that of a form of society, in which exploitation and war reign, which leads, through its indifference to human values, to the catastrophic extermination of humanity.